Cd2+-triggered amide tautomerization produces a highly Cd2+-selective fluorescent sensor across a wide pH range. (October 2016) - Liu, Yang; Qiao, Qinglong; Zhao, Miao; Yin, Wenting; Miao, Lu; Wang, Liqiu; Xu, Zhaochao
Abstract: An NBD-derived fluorescent sensor termedCdTS was reported to sense Cd 2+ with very high binding selectivity and significant fluorescence turn-on signal selectivity (65 fold enhancement). The amide/di-2-picolylamine receptor binds Cd 2+ in an imidic acid tautomeric form, but binds most of other metal ions in an amide tautomeric form. The transformable ability makesCdTS have the specific selectivity for Cd 2+ . Additionally, CdTS can fluoresently and colorimetricly recognize Cd 2+ across a wide pH range from 4.5 to 11.5. Finally, we appliedCdTS to detect Cd 2+ in living cells. Graphical abstract: CdTS can fluoresently recognize Cd 2+ across a wide pH range. Highlights: Cd 2+ can trigger amide tautomerization in the amide-DPA receptor. The probe is extremely sensitive to Cd 2+ with 65-fold emission enhancement. The probe has an excellent selectivity for Cd 2+ . The probe can recognize Cd 2+ across a wide pH range from 4.5 to 11.5. The probe can image Cd 2+ in living cells.